2021
DOI: 10.1128/msystems.01381-20
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography, Assembly Patterns, Driving Factors, and Interactions of Archaeal Community in Mangrove Sediments

Abstract: As a key microbial community component with important ecological roles, archaea merit the attention of biologists and ecologists. The mechanisms controlling microbial community diversity, composition, and biogeography are central to microbial ecology but poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…The neutral community model fitted well for the bacterioplankton community with a moderate fitted value (R 2 = 0.630∼0.709). The fitted value indicated that stochastic process played only a moderate role in the community assembly process by comparing with other studies ( Chen et al, 2019 ; Zhang Z. F. et al, 2021 ; Zhang et al, 2022 ). Due to the heightening of the dam and the increase in the water level, the aquatic ecosystem in the DJR is in a process of reconstruction.…”
Section: Discussionmentioning
confidence: 51%
“…The neutral community model fitted well for the bacterioplankton community with a moderate fitted value (R 2 = 0.630∼0.709). The fitted value indicated that stochastic process played only a moderate role in the community assembly process by comparing with other studies ( Chen et al, 2019 ; Zhang Z. F. et al, 2021 ; Zhang et al, 2022 ). Due to the heightening of the dam and the increase in the water level, the aquatic ecosystem in the DJR is in a process of reconstruction.…”
Section: Discussionmentioning
confidence: 51%
“…Mangrove forests are spatially heterogeneous along distinct intertidal and depth gradients within which the physicochemical conditions can differ dramatically ( 25 , 56 ). In several studies on terrestrial and coastal soil microbiomes across different latitudes and ecosystems, environmental parameters (especially pH) were more influential on the community composition than geographic distance ( 11 , 36 , 43 , 57 ). Similarly, a continuity of the microbial community driven by environmental factors has also been proposed for the pelagic ocean, as well as for brackish water bodies ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of the local environmental conditions in determining the soil microbiome which have received increased attention recently ( 32 35 ). However, there is still limited research on the variation of these factors on a larger scale and little is known about the factors that influence bacterial community assembly in mangrove soils ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many of them cover different areas of a certain mangrove or compare pristine versus impacted ecosystems, demonstrating microbial shifts associated with preservation status in a local scale. In contrast, few researchers have considered microbial communities on a latitudinal scale ( Li et al, 2021 ; Zhang et al, 2021 ). Consequently, the factors regulating the biogeographical distribution of mangrove microbial communities remain understudied.…”
Section: Introductionmentioning
confidence: 99%